Time, Money, and Punishment: Institutional Racial-Ethnic Inequalities in Pretrial Detention and Case Outcomes: - Martinez, Brandon P. (Crime & delinquency, 2020)
While prior research finds that pretrial detention has downstream consequences for racial inequalities in conviction and sentencing, it is often conceptualized as a discrete event within the criminal justice system. This study instead argues that pretrial detention operates as a racial-ethnic stratification process across time. We assess whether temporal and monetary dimensions of pretrial produce and reinforce racial-ethnic disparities in pretrial and subsequent case outcomes. Results indicate that time and money significantly stratify defendants by race and ethnicity, where bond amounts increase time detained, and that time detained in turn reinforces racial inequalities in conviction and incarceration. Indicative of cumulative understandings of inequality, our study shows how time and money in pretrial detention perpetuate inequalities in the criminal justice system.